The predominant weed flora of cassava and sweet potato fields - Bordeos, Eden Abril 1947- (1974)
There is a universal appeal to raise more crops to cope with the rising prices of food and increasing population of man. In order to help solve the apparent food crisis, this study concentrates on the weed flora of cassava and sweet potato. It attempts to make a qualitative and quantitative estimate of the weed population of these two field crops.
Thesis (M.A.T.)--University of the Philippines, Quezon City.
Keywords: Weeds